2017
DOI: 10.5194/isprs-annals-iv-2-w2-115-2017
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of 3d Models for Cultural Heritage Structural Analysis – Some Critical Issues

Abstract: ABSTRACT:Cultural Heritage documentation and preservation has become a fundamental concern in this historical period. 3D modelling offers a perfect aid to record ancient buildings and artefacts and can be used as a valid starting point for restoration, conservation and structural analysis, which can be performed by using Finite Element Methods (FEA). The models derived from reality-based techniques, made up of the exterior surfaces of the objects captured at high resolution, are -for this reason -made of milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Despite some works that attempt at classifying DCH images by employing different kinds of techniques [33][34][35][36] already exist, there are still few researches who seek to directly exploit the Point Clouds of CH for semantic classification or segmentation through ML [37] or DL techniques. One of them is [38], where a segmentation of 3D models of historical buildings is proposed for FEA analysis, starting from Point Clouds and meshes. Barsanti et al tested some algorithms such as the region growing, directly on the Point Clouds, proving its effectiveness for the segmentation of flat and well-defined structures, nevertheless more complex geometries such as curves or gaps have not been correctly segmented and the computational times increased considerably.…”
Section: Classification and Semantic Segmentation In The Field Of Dchmentioning
confidence: 99%
“…Despite some works that attempt at classifying DCH images by employing different kinds of techniques [33][34][35][36] already exist, there are still few researches who seek to directly exploit the Point Clouds of CH for semantic classification or segmentation through ML [37] or DL techniques. One of them is [38], where a segmentation of 3D models of historical buildings is proposed for FEA analysis, starting from Point Clouds and meshes. Barsanti et al tested some algorithms such as the region growing, directly on the Point Clouds, proving its effectiveness for the segmentation of flat and well-defined structures, nevertheless more complex geometries such as curves or gaps have not been correctly segmented and the computational times increased considerably.…”
Section: Classification and Semantic Segmentation In The Field Of Dchmentioning
confidence: 99%
“…Many experiments were also carried out on 3D data at different scales [6,81,82]. Some works aim to define a procedure for the integration of architectural 3D models within BIM [1,5,83].…”
Section: Segmentation and Classification In Cultural Heritagementioning
confidence: 99%
“…Recent years have witnessed significant progress in automatic procedures for segmentation and classification of point clouds or meshes [2][3][4]. There are multiple studies related to the segmentation topic, mainly driven by specific needs provided by the field of application (Building Information Modeling (BIM) [5], heritage documentation and preservation [6], robotics [7] autonomous driving [8], urban planning [9], etc.) In the cultural heritage field, the identification of different components ( Figure 1) in point clouds and 3D meshes is of primary importance because it can facilitate the study of monuments and integrating them with heterogeneous information and attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Barsanti et al [35] evaluated a region-growing algorithm to group points into clusters based on the angular comparison between locally estimated surface normals. They concluded that working on PCs does not seem to be the most suitable approach for creating a 3D segmentation to analyze historic concrete structures.…”
Section: Limitations Of Previous Workmentioning
confidence: 99%